(untitled) (Research, Society and Development, 2021)
Birds of prey are predatory birds are present in all states of Brazil, especially of Rupornis magnirostris. This bird has a very diverse diet presents an extremely territorial behavior, respecting when are withdraw from nature and raised in captivity, they are change their behavior so that they are able to adapt to the new middle. In this way, this study has the objective the elaboration of the ethogram of Rupornis magnirostris captive in order to add more information available on the biology and behavior of this species in captivity. For this, an ethogram was performed using the ad libitum technique performed in 3 shifts lasting 30 minutes each and after this, the Focal-Animal technique was used, divided into 3 shifts, lasting 30 minutes, performed in 21 sessions, during 10 days. Obtaining as a result the neutral position behavior the most expressed result of the lack of environmental enrichment and stimulus. Therefore, the ambience and physical conditions of the hawks are extremely important to understand the behavior of this species in captivity.